2019
DOI: 10.3847/1538-4357/ab3d36
|View full text |Cite
|
Sign up to set email alerts
|

Disk–Jet Coupling in the 2017/2018 Outburst of the Galactic Black Hole Candidate X-Ray Binary MAXI J1535–571

Abstract: MAXI J1535−571 is a Galactic black hole candidate X-ray binary that was discovered going into outburst in 2017 September. In this paper, we present comprehensive radio monitoring of this system using the Australia Telescope Compact Array (ATCA), as well as the MeerKAT radio observatory, showing the evolution of the radio jet during its outburst. Our radio observations show the early rise and subsequent quenching of the compact jet as the outburst brightened and then evolved towards the soft state. We constrain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
152
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(191 citation statements)
references
References 112 publications
24
152
1
Order By: Relevance
“…Both would result in optically thin radio emission due to internal shocks (Kaiser et al 2000;Miller-Jones et al 2009;Jamil et al 2010;Malzac 2014). Fender et al (2009), Miller-Jones et al (2012, and Russell et al (2019) looked in detail at possible connections between the occurrence of radio flares and changes in the X-ray timing properties in several transient BH LMXBs: XTE J1550-564, XTE J1859+226, GX 339-4, H1743-322, XTE J1752-223, and MAXI J1535-571. Despite some cases in which a radio flare occurred close in time (within ∼half a day to days) to the disappearance of type-C QPOs and/or the appearance of type-B QPOs, the authors concluded that there was not enough evidence to directly tie discrete jet ejections to a change in X-ray timing properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both would result in optically thin radio emission due to internal shocks (Kaiser et al 2000;Miller-Jones et al 2009;Jamil et al 2010;Malzac 2014). Fender et al (2009), Miller-Jones et al (2012, and Russell et al (2019) looked in detail at possible connections between the occurrence of radio flares and changes in the X-ray timing properties in several transient BH LMXBs: XTE J1550-564, XTE J1859+226, GX 339-4, H1743-322, XTE J1752-223, and MAXI J1535-571. Despite some cases in which a radio flare occurred close in time (within ∼half a day to days) to the disappearance of type-C QPOs and/or the appearance of type-B QPOs, the authors concluded that there was not enough evidence to directly tie discrete jet ejections to a change in X-ray timing properties.…”
Section: Discussionmentioning
confidence: 99%
“…Within a few days of the (occasionally rapid) changes between the various types of low-frequency QPOs, radio flares have been observed in some BH LMXBs (see, e.g., Corbel et al 2001;Brocksopp et al 2002;Gallo et al 2004;Miller-Jones et al 2012;Russell et al 2019). The flares last hours to days and high angular-resolution radio and X-ray observations have shown that they are the result of discrete ejection events that occurred prior to the radio flares (Corbel et al 2003, 2005, andreferences above).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an X-ray luminosity of jets varying between 1-5% L edd (Maccarone 2003;Miller-Jones et al 2012;Curran et al 2014;Russell et al 2019), the A-parameter normalization estimated by Fender et al (2005) in this relation (see Table 1), and a mean δ t estimated from the WATCHDOG catalogue as discussed above, we are able to compute an L CR estimate via Equation 2.…”
Section: Population and Cr Power Of Galactic Xrbsmentioning
confidence: 99%
“…However, it was also discovered that in some accretion state regimes (which empirically reveal themselves as X-ray states defined by their spectral and variability properties; see Belloni 2010, and references therein) the jets are suppressed, possibly absent (namely soft X-ray states, e.g. Fender et al 1999;Coriat et al 2011;Russell et al 2011Russell et al , 2019. Prior to this quenching of the jets, bright radio flares are often reported, which are sometimes resolved into discrete ejecta (e.g.…”
mentioning
confidence: 99%